Evidence and Sustenance in Transnational Indigenous Literatures - Mishra, Ananya (University of Cambridge, 2021)
The thesis compares literatures from two political contexts, the postcolonial Indian nation-state and the settler colonial states, Australia and North America. I examine the ways in which Indigenous sovereignty and transnational solidarity is established in literature. This thesis demonstrates that Indigenous demand for land redress is inseparable from claims to literary sovereignty. I theorise a paradox of evidence—between the state’s erasure of Indigeneity and colonial knowledge that objectifies Indigeneity to appropriate it in claims of nationhood—that facilitated imperial acquisition of Indigenous land. I argue that the post- independence Indian nation-state replicates this paradox for similar purposes. The thesis studies how Indigenous writers reformulate the literary as evidentiary to resist continued colonisation by the global industrial complex, and intellectual colonisation by the dominant Euro- American and Hindu nationalist discourse in national institutions (universities, museums, and archives). Accordingly, the thesis places Adivasi writings from India in conversation with Native American and Australian First Nations literatures and methods. Chapter 1 provides literary readings on evidence. I explore the “archival poetics” (AP1) and “ethnographic refusal” (A. Simpson 95) in the works of Hansda Sowvendra Shekhar, Jeanine Leane, Natalie Harkin, and Wendy Rose. Chapter 2 explores the literary manifestation of land-based Indigenous philosophies. I examine Adivasi mythology as political discourse and study the transnational scope of Simon Ortiz’s poetry to query the future poetics of the Adivasi factory worker. Chapter 3 focuses on Indigenous literary evidence of the climate crisis. I compare the poetry of Joan Naviyuk Kane and Jacinta Kerketta to study the imagination of absence of jal, jangal, jameen (water, forest, land), and ice. I historicise the recurrent environmental slogan jal, jangal, jameen as climate vocabularies. Lastly, I provide a literary reading of Adivasi philosophies of the non-human ...